Optimal sequencing and lot sizing in a multi-model synchronous assembly line - Cafaro, Diego C. (2014)
This work presents a mixed-integer nonlinear mathematical pro-gramming (MINLP) model aiming at optimizing the sum of transition and in-ventory carrying costs in a multi-model synchronous assembly line. Different products are assembled in the same line in runs or campaigns, whose sequence and length should be optimally determined. As products show different cycle times, transition periods are of particular interest due to the productivity reduc-tion. The proposed model precisely accounts for transient periods, at the time it incorporates further details such as semi-elaborate stocks. It is successfully ap-plied to a real-world case study of the argentine truck trailer industry.